A survey of infections in United Kingdom laboratories, 1994-1995. - Walker, D (1999)
AIMS: To identify the number and type of infections occurring in United Kingdom clinical laboratories during 1994 and 1995, following similar surveys covering 1970 to 1989. METHODS: A retrospective questionnaire survey was undertaken of 397 responding UK clinical laboratories covering 1994 and 1995. A follow up telephone survey was undertaken with each of the laboratories from which a questionnaire had been received indicating a possible or probable laboratory acquired infection during 1994 or 1995. RESULTS: Questionnaires were sent to 659 laboratories or organisations which were thought to have laboratories, of which 557 responded (response rate of 84.5%). Of these, only 397 were from organisations with laboratories. Over 55,000 person-years of occupational exposure were covered, and only nine cases identified, giving an infection incidence rate overall of 16.2/100,000 person-years, compared with 82.7 infections/100,000 person-years found in a similar survey covering 1988 and 1989, reported previously. Infections were commonest in females, in relatively young staff, in microbiology laboratory workers, and in scientific/technical employees. Gastrointestinal infections predominated, particularly shigellosis, but few specific aetiological factors relating to working practices were identified. No hepatitis B cases were reported. CONCLUSIONS: The small number of cases identified indicates high standards of infection control, though there is still room for improvement. Periodic studies of this kind are not adequate for comprehensive monitoring of the incidence of laboratory acquired infections. That will require the introduction of a routine, active surveillance programme or prospective survey which has the support and commitment of the laboratories themselves.